Intranasal Corticosteroids Do Not Lead to Ocular Changes: A Systematic Review and Meta‐analysis. (19th September 2018) - Valenzuela, Carla V.; Liu, James C.; Vila, Peter M.; Simon, Laura; Doering, Michelle; Lieu, Judith E. C.
Abstract : Objectives: The safety and efficacy of intranasal corticosteroids (INCS) are well established, but there remains apprehension that INCS could lead to systemic side effects, as with oral steroids. The objective of this systematic review was to assess whether the use of INCS lead to increased intraocular pressure (IOP) above 20 mm Hg, glaucoma, or formation of posterior subcapsular cataracts in adult patients with rhinitis. Methods: Two medical librarians searched the published literature for records discussing the use of "nasal steroids" in "rhinitis" and their effect on "intraocular pressure, " "cataracts, " or "glaucoma." Results: A total of 484 studies were identified, and 10 randomized controlled trials met our inclusion criteria. Meta‐analysis of 2, 226 patients revealed that the relative risk of elevated IOP in those who received INCS was 2.24 (95% confidence interval [CI]: 0.68 to 7.34) compared to placebo. The absolute increased incidence of elevated IOP in patients using INCS compared to placebo was 0.8% (95% CI: 0% to 1.6%). There were zero cases of glaucoma in both placebo and INCS groups at 12 months. The absolute increased incidence of developing a posterior subcapsular cataract was 0.02% (95% CI: −0.3% to 0.4%). Conclusions: Use of INCS is not associated with a significant risk of elevating IOP or developing a posterior subcapsular cataract in patients with allergic rhinitis. Presence of glaucoma, however, is the real clinical adverse event of concern. There were zero reported cases of glaucoma at 12 months. Future studies should formally evaluate for glaucoma rather than use IOP measures as a surrogate. Laryngoscope, 129:6–12, 2019